Characteristics of Organizational Learning Culture in Serbian Elite Team Sports - Radenko M. Matic; Nebojsa Maksimovic (Journal of Anthropology of Sport and Physical Education, 2020)
Organizational culture represents employees' integrated values and business orientation of employees in the work environment, and conduct unwritten and written rules. This research aimed to evaluate the characteristic of organizational learning culture in Serbian team sports. The sample of respondents in this study consisted of 118 available managers of different levels in the organizational structure of sports organizations from four selected team sports (football, basketball, handball, and volleyball), which institutionally belong to the highest rank of the competition. At the individual level, the authors revealed the differences in favor of managers in volleyball clubs that come from better support, openness, and feedback from each other in the organization, all for their career development (χ2=12,79, p<0.01). From another side, the organizational level's key differences come from the availability of information to all, better resource management, initiative recognition, openness to cooperation, and leadership (χ2=11,33, p<0.01). Based on the obtained results, the authors discussed the theoretical and practical values of research.